PERAN PENDIDIKAN TERHADAP SISWA DALAM PENCEGAHAN PERILAKU CYBER BULLYING DI ERA DIGITAL - J.A Pakai, asra (Moderasi: Jurnal Studi Ilmu Pengetahuan Sosial, 2021)
Cyber ​​bullying is the impact of the development of technology that triggers an increase in internet use. The author discusses the role of education to students in preventing cyber bullying behavior in the digital era. Education currently refers to character education as regulated in Law Number 20 of 2003 concerning the National Education System which aims to form a strong personality in accordance with the identity of the Indonesian nation. The problem in this research: how is the role of education to students in preventing cyber bullying behavior in the digital era. Qualitative research methods. From the research above, it can be concluded that cases of cyber bullying among students have become commonplace in this digital era, especially in the free use of social media by students. For the student who becomes the perpetrator, this will be a joke, but it is different from the student who becomes a victim because it will have an impact until he grows up which can weaken his mentality so that he feels a victim of inferiority. This is where the important role of educators is to provide behavioral direction, good speech, mental motivation for victims.